TIM Proteins and Immunity - Kane, Lawrence P. (2010)
Proteins of the transmembrane immunoglobulin and mucin domain (TIM) family are expressed by multiple cell types within the immune systems of rodents and humans. Studies over the last several years have suggested that these proteins may be promising targets for therapeutic manipulation of immune responses. This review discusses the progress that has been made in understanding TIM protein function in the immune system, as well as some of the unresolved issues that remain on the road to eventually targeting TIM proteins for enhancing or inhibiting immunity.